(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2016)
The text retraces the current debate around the notions of post-cinema and post-media. Employing a dialogic approach, the editors propose a theoretical framework to provide context for the main contributions on these topics published in recent years, highlighting the conceptual connections to the previous scholarship. The resulting reflection serves as a platform to introduce and situate the contributions to this special issue. In particular, the editors propose to use the term configuration to account for the various aspects and facets of contemporary cinematic experience.